CT colonography: detection of lesions and patients’ preference: correlation with standard colonoscopy - Che Mohamed, Siti Kamariah; Abd. Aziz, Azian; Md Ralib @ Md Raghib, Ahmad Razali; Hassan, Radhiana; Md Nor, Azmi; Mohd Rus, Razman; Mohd Yusof, Mubarak; Abdul Rahman, Zainun (2014)
The aim of the study is to measure the prevalence and types of abnormalities on CT Colonogra- phy, and to assess the association between standard colonoscopy and CT Colonography. Another aim of the study is to determine the level of preference between standard colonoscopy and CT Colonography. Materials and Method A total of 24 patients were included in the study. All pa- tients underwent a standard bowel preparation (phospho-soda/Fleet@). Patients underwent CTC within 4 hours after standard colonoscopy. Sucient amount of air was insuated through rectal tube for colonic distension prior to scanning. CTC was performed using a 4detector row helical CT scanner (Somatom Volume Zoom). Image acquisition was done in prone and supine positions. Scanning parameters were as per CTC protocal. The images were transferred to a remote syngo Colon Work ow Assisstant workstation for 2D and 3D data rendering. The endoluminal navi- gations were performed from rectum to caecum, in both retrograde and antegrade directions in order to visualize both sides of haustral folds. CTC ndings were correlated with conventional colonoscopy ndings, which were used as standard reference. For assessment of patients preference between CTC and standard colonoscopy, standard questionnaires were given to patients after both CTC and standard colonoscopy procedures. Results: A total of 24 patients were included in this study. Most of the patients were male (66.7%), and majority were Malays (70.8%). Age ranges from 20-70 years, but most of the patients were more than 40 years of age. Per rectal bleeding were the most common indication for colonoscopy (29.2%). Abnormal CTC results were detected in 62.5%. Abnormal results were due to tumour in 29.2%, polyp in 25% and diverticulum in 8.3%. Correlating with standard colonoscopy results, there is no signicant association between the two studies (P value = 0.092). For level of preference between CTC and standard colonoscopy and nal selection between these two procedures, most of the patients were satised with CTC procedure, which was 62.5%. Conclusion: Even though there were variations in the detection rates of CTC in various studies, results may improve further with ongoing technical improvements and increasing experience. As there is increasing demand of endoscopic units for colorectal cancer screening, CTC oers an eective alternative especially in symptomatic patients and may become an important screening method for colorectal cancer in future. Furthermore, CTC has higher acceptability to patients due to its advantages over standard colonoscopy.